2017
DOI: 10.1186/s12891-017-1704-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome following additional rhBMP-7 application in revision surgery of aseptic humeral, femoral, and tibial shaft nonunion

Abstract: BackgroundSurgical revision concepts for the treatment of aseptic humeral, femoral, and tibial diaphyseal nonunion were evaluated. It was analyzed if the range of time to bone healing was shorter, and if clinical and radiological long-term outcome was better following application of additional recombinant human Bone Morphogenetic Protein-7 (rhBMP-7) compared to no additional rhBMP-7 use.MethodsIn a retrospective comparative study between 06/2006 and 05/2013, 112 patients diagnosed with aseptic diaphyseal humer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
0
27
0
2
Order By: Relevance
“…Finally, 5 randomized controlled trials (RCTs) [15][16][17][18][19] and 4 nonrandomized controlled trials [20][21][22][23] were included in the systematic review and meta-analysis, most of which were small sample size studies of 30-124 cases, with a total of 655 nonunion cases. These 9 studies [15][16][17][18][19][20][21][22][23] reported on 11 trials as one (Hackl et al [23]) reported 3 clinical trials. The observation group was treated with BMP plus autologous bone in 5 studies, BMP alone in 2 studies, and BMP combined with natural inorganic bone in one study.…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, 5 randomized controlled trials (RCTs) [15][16][17][18][19] and 4 nonrandomized controlled trials [20][21][22][23] were included in the systematic review and meta-analysis, most of which were small sample size studies of 30-124 cases, with a total of 655 nonunion cases. These 9 studies [15][16][17][18][19][20][21][22][23] reported on 11 trials as one (Hackl et al [23]) reported 3 clinical trials. The observation group was treated with BMP plus autologous bone in 5 studies, BMP alone in 2 studies, and BMP combined with natural inorganic bone in one study.…”
Section: Search Resultsmentioning
confidence: 99%
“…There is evidence that the application in a clinical setting leads to consolidation of bone defects, even in cases of delayed healing or non-union [ 14 , 15 , 16 ]. However, the clinical results are controversial: While some authors report positive effects of BMP-7 application on bone healing, other studies did not find a positive influence on bone defect consolidation when BMP-7 was used [ 14 , 17 , 18 , 19 , 20 ]. Using the currently available application form of collagen-incorporated BMP-7 applied to the defect site does not guarantee a continuous stimulation of the local cells by long-lasting BMP-7 release [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…BMPs belong to TGF-β family, and BMP-2(Infuse ® , Minneapolis, MN; Crockett, Rogers, Coxon, Hocking, & Helfrich, 2011) and BMP-7 (OP-1 ® , Olympus, MA) are FDA approved for clinical use (Burkus, Heim, Gornet, & Zdeblick, 2003;McKay, Peckham, & Badura, 2007). Hackl et al (2017) used rhBMP-7 for local administration in 62 out of 112 patients diagnosed with aseptic diaphyseal humerus (22 patients), femur (41 patients), and tibia (49 patients) nonunion. The rhPDGF (Augment ® Bone Graft, BioMimetic Therapeutics, TN) is also commercially available and uses β-tricalcium phosphate as the carrier vehicle (McKay et al, 2007) and has used to treat foot, ankle, and distal radius fractures clinically and it is currently under review by the FDA, and is commercially available in the US.…”
Section: Number Of Clinical Studies Was Conducted To Support the Use Ofmentioning
confidence: 99%
“…There is a large amount of preclinical trial information to support the use of BMPs to induce differentiation of stem cells into osteoprogenitor cells or enhance overall osteogenic activity in accelerating bone healing. Hackl et al (2017) used rhBMP-7 for local administration in 62 out of 112 patients diagnosed with aseptic diaphyseal humerus (22 patients), femur (41 patients), and tibia (49 patients) nonunion. White et al (2007) (Aro et al, 2011).…”
mentioning
confidence: 99%